Extracellular Vesicle Proteins and MicroRNAs Are Linked to Chronic Post-Traumatic Stress Disorder Symptoms in Service Members and Veterans With Mild Traumatic Brain Injury - Guedes, Vivian A.; Lai, Chen; Devoto, Christina; Edwards, Katie A.; Mithani, Sara; Sass, Dilorom; Vorn, Rany; Qu, Bao-Xi; Rusch, Heather L.; Martin, Carina A.; Walker, William C.; Wilde, Elisabeth A.; et al. (Frontiers in Pharmacology, 2021)
Symptoms of post-traumatic stress disorder (PTSD) are common in military populations, and frequently associated with a history of combat-related mild traumatic brain injury (mTBI). In this study, we examined relationships between severity of PTSD symptoms and levels of extracellular vesicle (EV) proteins and miRNAs measured in the peripheral blood in a cohort of military service members and Veterans (SMs/Vs) with chronic mTBI(s). Participants (n=144) were divided into groups according to mTBI history and severity of PTSD symptoms on the PTSD Checklist for DSM-5 (PCL-5). We analyzed EV levels of 798 miRNAs (miRNAs) as well as EV and plasma levels of neurofilament light chain (NfL), Tau, Amyloid beta (Aβ) 42, Aβ40, interleukin (IL)-10, IL-6, tumor necrosis factor-alpha (TNFα), and vascular endothelial growth factor (VEGF). We observed that EV levels of neurofilament light chain (NfL) were elevated in participants with more severe PTSD symptoms (PCL-5≥38) and positive mTBI history, when compared to TBI negative controls (p=0.024) and mTBI participants with less severe PTSD symptoms (p=0.006). Levels of EV NfL, plasma NfL, and hsa-miR-139-5p were linked to PCL-5 scores in regression models. Our results suggest that levels of NfL, a marker of axonal damage, are associated with PTSD symptom severity in participants with remote mTBI. Specific miRNAs previously linked to neurogenerative and inflammatory processes, and glucocorticoid receptor signaling pathways, among others, were also associated with the severity of PTSD symptoms. Our findings provide insights into possible signaling pathways linked to the development of persistent PTSD symptoms after TBI and biological mechanisms underlying susceptibility to PTSD.